SEXUAL VIOLENCE WITHIN THE FAMILY AGAINST CHILDREN AND ADOLESCENTS: LEGAL CONSEQUENCES AND CHALLENGES (Editora Impacto Científico, 2025)
Sexual violence within the family remains one of the most recurrent forms of aggression against children and adolescents, with close relatives such as parents, grandparents, and uncles often identified as perpetrators. Despite the existence of legal norms aimed at preventing and punishing such practices, the reality is marked by silence and underreporting, which hinders accountability and victim protection. This article seeks to analyze intrafamilial sexual violence from the perspective of its legal consequences and the challenges involved in addressing it. Specifically, it aims to present a brief historical overview of sexual violence against children and adolescents, examine the crimes established in Brazilian law, identify the civil repercussions of such cases, and discuss the obstacles that prevent effective solutions. The study is based on bibliographic research supported by theoretical discussions on the subject, as well as the analysis of official statistical data. The article is structured to facilitate clear presentation of facts and critical reflection, covering the historical background, legal framework, civil consequences, and challenges in confronting intrafamilial sexual violence.DOI: https://doi.org/10.56238/edimpacto2025.090-066